Dispersi Padat untuk Peningkatan Laju Disolusi Natrium Diklofenak dengan Variasi Konsentrasi Polivinil Pirolidon K30 - Noval Noval; Rosyifa Rosyifa (Jurnal Surya Medika (JSM), 2021)
Diclofenac sodium is included in the class II category based on the biopharmaceutics classification system (BCS), sodium diclofenac has low solubility and high permeability. Low solubility will affect the absorption of drugs in the body because the rate of dissolution will decrease. Polyvinyl Pyrrolidone (PVP) K30 is an inert carrier that dissolves easily in water and can affect the solubility of an active drug substance. To know solid dispersion system increasing dissolution rate of sodium diclofenac by adding variations concentration of PVP K30. Solid dispersion uses a solvent method with variations concentration of PVP K30 1:3, 1:5, 1:7, and 1:9. Test physical properties of solid dispersions using a moisture test and compressibility. Solid dispersion dissolution test using type 2 dissolutions test and determination of concentration using UV-VIS spectrophotometry. Test results were analyzed using One Way ANOVA and continued test. Solid dispersion has a good physical whit moisture percentage not >5% and compressibility not >20%. Solid dispersion of sodium diclofenac with the addition of PVP K30 can increase dissolution rate compared to pure sodium diclofenac (p<0,05) with the highest ratio 1:7. Each comparison has a significant difference (p<0,05) except in ratio 1:9. Solid dispersion of sodium diclofenac with PVP K30 can increase the dissolution rate of pure sodium diclofenac.